Analysis and assessment of the validity dough "theory of functions of the complex variable" - Lidiya A. Muratova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In article the analysis of quality of the "Theory of Functions of a Complex Variable" test is carried out. The dough validity in normal way to distribution, according to the contents, on the distinguishing ability is estimated. The look and proportions of a curve of distribution of the gained points testifies in favor of normal distribution. The test rather fully and deeply reflects the studied material that allows to draw a conclusion on its substantial validity. For quality check of dough on the distinguishing ability two numerical characteristics for each task are found: dot biserial coefficient and coefficient of a diskriminativnost’. The subsequent analysis showed that only two tasks don't satisfy to one of goodness conditions. Thus average value of that different authors offer was considered as a critical point. Having analyzed the maintenance of tasks, it is offered to process one of them, and to keep another.